The mediating and moderating role of planning on mothers' decisions for early childhood dietary behaviours. Issue 12 (2nd December 2017) - Hamilton, Kyra; Kothe, Emily J.; Mullan, Barbara; Spinks, Teagan
Abstract : Objective: Examine the roles of action and coping planning on the intention–behaviour relationship for mothers' decisions for their young children's dietary behaviours. Design: Prospective design with two waves of data collection, one week apart. Main outcome measures: Mothers ( N  = 197, M age  = 34.39, SD  = 5.65) of children aged 2–3 years completed a main questionnaire assessing planning constructs and intentions, and a one-week follow-up of the target behaviours – 'healthy eating' and 'discretionary choices'. Results: Intention was the strongest predictor of behaviour for both dietary behaviours. For healthy eating, intention moderated the indirect relationship between intention–behaviour via planning; coping planning was less important when intention was strong. Further, intention was not a direct predictor of behaviour when intention was relatively low. Action planning was not a direct predictor of either behaviour after accounting for intention and coping planning; action planning on behaviour was mediated by coping planning (only for healthy eating). Intention was not a direct predictor of coping planning; intention on coping planning was mediated by action planning. Neither type of planning predicted discretionary choices. Conclusion: Current findings contribute novel information on the mechanisms underpinning the effect of action and coping planning on the intention–behaviour relationship.